Normative values of the brief international cognitive assessment for multiple sclerosis (BICAMS) in an Italian young adolescent population: the influence of age, sex, and education - Falco, Fabrizia; Lamagna, Federica; Eliano, Martina; di Monaco, Cristina; Trojano, Luigi; Lus, Giacomo; Moccia, Marcello; Lauro, Francesca; Liccardo, Tiziana; Chiodi, Alessandro; Carotenuto, Antonio; Morra, Vincenzo Brescia; et al. (Neurological sciences, 2025)
Background The Brief International Cognitive Assessment for Multiple Sclerosis (BICAMS) is the most widely used in clinical practice and the least time-consuming battery to estimate cognitive function in adults with Multiple Sclerosis (MS), while it has been included in few studies on young MS, also because of the absence of normative values. Objective The aim of this study is to evaluate the impact of age, sex and education on BICAMS scores in a young adolescent population. Methods We administered the BICAMS to 169, 11-to-18-year-old, healthy subjects. Linear regression models were used to assess the impact of age, sex, and education on sub-test scores. When statistically significant ( p < 0.05), we used the regression coefficient to correct the raw scores. Results younger age was associated with worse performance on SDMT ( β = 1.76; p < 0.05), CVLT-II ( β = 3.33; p < 0.05) and BVMT-R ( β = 0.62; p < 0.05). Female sex was associated SDMT ( β = 2.75 ( p < 0.05) and CVLT-II ( β = 2.51 ( p < 0.05). Educational attainment was associated with better performance on SDMT ( β = 1.79 ( p = < 0.05) and BVMT-R ( β = 0.61; p < 0.05). Cut-off points were suggested at the 5th lowest percentile. Conclusion Age, sex, and education must be accounted for when applying the BICAMS to young population. Its use in everyday assessment of patients with Pediatric Onset Multiple Sclerosis (POMS) could help to compare and combine data across centers, identifying patients requiring a comprehensive evaluation and ad hoc cognitive stimulation programs.